2006
DOI: 10.1007/s11663-006-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron ore reduction in a continuously operated multistage lab-scale fluidized bed reactor—Mathematical modeling and experimental results

Abstract: Industrial-scale fluidized bed processes for iron ore reduction (e.g., FIOR and FINMET) are operated by continuous feeding of ore, while laboratory tests are mostly performed under batchwise operation. The reduction behavior under continuous operation is influenced by both the residence time of the iron ore particles and the reduction kinetics, which is obtained by batch tests. In a mathematical model for such a process, the effect of both phenomena has to be considered. The residence time distribution of iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…To gain these parameters subjected to temperature and reduction gas compositions, complex experimental investigations are required. 1,2 For optimal selection of test operating conditions, 3 reduction diagrams of the system Fe, Fe 32d O 4 , Fe 12y O, H 2 , H 2 O, CO and CO 2 have to be calculated. The objectives of this work are to describe empirical calculation methods for reduction diagrams and amounts of non-stoichiometries for the iron oxides magnetite and wustite.…”
Section: Introductionmentioning
confidence: 99%
“…To gain these parameters subjected to temperature and reduction gas compositions, complex experimental investigations are required. 1,2 For optimal selection of test operating conditions, 3 reduction diagrams of the system Fe, Fe 32d O 4 , Fe 12y O, H 2 , H 2 O, CO and CO 2 have to be calculated. The objectives of this work are to describe empirical calculation methods for reduction diagrams and amounts of non-stoichiometries for the iron oxides magnetite and wustite.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Hence, it is assumed that the mass transfer resistance of gases from the bulk to the surface can be neglected. Thurnhofer 18) conducted microscopical analyses of polished sections of reduced iron ore fines and observed that a high amount of pores were spread through the entire fine. The fine is subdivided into small grains (2 to 10 μm) surrounded by the pores.…”
Section: )mentioning
confidence: 99%
“…In this context, a huge number of models have already been developed trying to represent the DR process. These models range from singleparticle approaches to multiparticle and components models with topochemical and grain models (Venkateswaran and Brimacombe, 1977, Yu and Gillis, 1981, Takenaka and Kimura, 1986, Negri, 1991and 1995, Parisi and Laborde, 2004, Piotrowski et al, 2005, , Pineau et al, 2006, Thurnhofer, 2006, Valipour et al, 2006, Ajbar et al, 2011, Nouri, 2011, Costa et al, 2013, Shams and Moazeni, 2015, Kazemi, 2017, Castro, 2018, Rocha et al, 2019. Since the DR process can be summarized as a counter-current bed composed of solid and gas into a mass and heat transfer, the most acceptable and useful models correspond to numerical models that comprise the multi interaction and multiple phase theory.…”
Section: Introductionmentioning
confidence: 99%